The Effectiveness of Mind Mapping in Improving Understanding of Ethical Values in Islamic Religious Education Learning - Hafilatul Hasanah (Khatulistiwa Insight: Islamic Education and Learning, 2025)
The challenge in Islamic Education learning is a deep understanding of Islamic ethical values. However, the challenge faced in this education is how to deliver the material effectively so that students not only understand the religious concepts but are also able to apply those ethical values in their practice. One method that has emerged as an alternative in improving learning effectiveness is Mind Mapping. Despite the use of learning media, the lack of variety in teaching methods often reduces student activity and makes the learning atmosphere less interesting. Learning methods that focus on lectures and memorization make it difficult for students to understand the material deeply, so students' understanding of ethical values in PAI learning becomes less than ideal. This study aims to evaluate the effectiveness of mind mapping as a method to improve understanding of ethical values in PAI learning at SMPN 2 Krejengan. The research method used qualitative research with a case study approach carried out at SMPN 2 K Rejengan, while the stages in the research were observation, interviews and documentation and then processed using data. Data were collected through tests of understanding of ethical values before and after the intervention, as well as collecting students' perceptions of the use of mind mapping in PAI learning. The results of the study showed that the use of mind mapping significantly improved the understanding of Islamic ethical values. However, the use of mind mapping at SMPN 2 Krejengan not only increased students' understanding of ethical values in Islam, but also received positive support from students as an effective and fun learning tool. And there are some students who consider mind mapping as a less effective technique in certain cases, especially if it is not supported by adequate teaching or if there are obstacles in understanding the mind map structure created by the teacher.